Basal Cell Carcinoma Masked in Rhinophyma. (10th June 2013) - De Seta, Daniele; Russo, Francesca Yoshie; De Seta, Elio; Filipo, Roberto
Abstract : Rhinophyma, the advanced stage of rosacea, is a lesion characterized by progressive hypertrophy and hyperplasia of sebaceous glandular tissue, connective tissue, and blood vessels. Rhinophyma can lead to a significant facial disfigurement and severe emotional distress, but it is not only an aesthetic problem, since rare cases of simultaneous presence of malignant tissue are described in the literature. The case of an 84-year-old farmer affected by basal cell carcinoma (BCC) and diagnosed in the context of rhinophyma is presented. The anatomical distortion produced by the chronic inflammation and fibrous scarring makes the BCC diagnosis difficult and uncertain. The histological examination of the entire mass and its margins is fundamental. A partial biopsy can lead to a false negative result, and the histological examination must be repeated intra- or postoperatively.